2021
DOI: 10.1155/2021/3946875
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of KRAS Gene Mutation on Survival of Patients with Peritoneal Metastases of Colorectal Adenocarcinoma

Abstract: Objective. The main objective of the study was to determine the effect of the presence of mutation in the KRAS gene on the survival in patients with colorectal cancer (CRC) and peritoneal metastases (PM). Materials and Methods. A retrospective cohort study was performed. Patients diagnosed with CRC with synchronous or metachronous PM between January 2006 and December 2019 were included. Data on the histopathological, clinical, and treatment factors were collected. The effect of each variable on survival was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Younger patients (65 years) with intermediate stages (T3N1) and with an intermediate PCI (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) more frequently developed peritoneal metastasis during follow-up. This observation may be attributed to the fact that these patients had longer surveillance times and could make an early diagnosis of peritoneal metastasis in cases of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Younger patients (65 years) with intermediate stages (T3N1) and with an intermediate PCI (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) more frequently developed peritoneal metastasis during follow-up. This observation may be attributed to the fact that these patients had longer surveillance times and could make an early diagnosis of peritoneal metastasis in cases of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of PCI values demonstrated that patients with the presence of SPM had a higher PCI (>20) (57 patients, 43.1%), while those with MPM had intermediate PCI values (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) (46 patients, 42.5%) (p = 0.014).…”
Section: Patient and Tumor Characteristics Categorized By Spm/mpm Tim...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research highlights that prognostic information on the Kirsten Rat Sarcoma Virus (KRAS) mutation is critical for patient survival. It has also been identified that the most prolonged survival rate of patients with KRAS mutation at 36 months was only 24 percent (72). In this case, integrating artificial intelligence (AI) helps evaluate all the complex heterogeneous tumor information and patterns acquired from biomarker sensing NPs to devise an accurate treatment plan and aid in the faster detection of mutations, classifying mutated and non-mutated biomarkers, better drug and protein interaction for greater drug efficacy and improved drug delivery.…”
Section: Predicting Anticancer Drug Synergymentioning
confidence: 99%